Maternal Substance Abuse and the Later Risk of Fractures in Offspring: L'abus maternel de substances et le risque ultérieur de fractures chez les enfants. (June 2021) - Auger, Nathalie; Low, Nancy; Ayoub, Aimina; Lee, Ga Eun; Luu, Thuy Mai
Objective: To assess the association of maternal illicit drug abuse before or during pregnancy with future fractures in offspring. Methods: We performed a longitudinal cohort study of 792, 022 infants born in hospitals of Quebec, Canada, between 2006 and 2016, with 5, 457, 634 person-years of follow-up. The main exposure was maternal substance abuse before or during pregnancy, including cocaine, opioid, cannabis, and other illicit drugs. The main outcome measure was hospitalization for traumatic fracture in offspring up to 12 years of age. We used adjusted Cox regression models to compute hazard ratios (HR) and 95% confidence intervals (CI) for the association of maternal drug abuse with the subsequent risk of fracture in children. Results: The incidence of child fractures was higher for maternal illicit drug abuse than no drug abuse (21.2 vs. 15.4 per 10, 000 person-years). Maternal drug abuse before or during pregnancy was associated with 2.35 times the risk of assault-related fractures (95% CI, 1.29 to 4.27) and 2.21 times the risk of transport accident-related fractures (95% CI, 1.34 to 3.66), compared with no drug abuse. Associations were strongest before 6 months of age for assault-related fractures (HR = 2.14; 95% CI, 0.97 to 4.72) and after 6 years for transport-related fractures (HR = 2.86; 95% CI, 1.35 to 6.05). Compared with no drug abuse, associations with assault and transport-related fractures were elevated for all drugs including cocaine, opioids, and cannabis. Conclusions: Maternal illicit drug abuse is associated with future child fractures due to assault and transport accidents.